Efforts to Settle Disputes on Employee Severance Pay in Companies According to the Manpower Act No. 13 of 2003 - Dela Ayu Septia Monica; Sri Anggraini Kusuma Dewi; Gesang Iswahyudi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
Disputes or disputes can occur in every human relationship, even considering that legal subjects have long known legal entities, the more parties involved in them. The purpose of this study is to resolve disputes regarding severance pay between workers, laborers and employers. Research Methods The used by the author in conducting this research is using a sociological empirical method. The empirical sociological method is a research that views law as a social phenomenon. Meanwhile, from its nature, this research is a descriptive analysis research. Descriptive method can be interpreted as a problem solving process that is investigated by describing or describing the state of the subject or object of the researcher, namely: a person, institution, community and others, and at the present time based on the facts that appear or as they are. Results According to Article 1 point 16 of Law Number 13 of 2003 concerning Manpower, industrial relations are a system of relations formed between actors in the process of producing goods and/or services consisting of elements of entrepreneurs, workers/laborers, and the government based on values. values ​​of Pancasila and the 1945 Constitution of the Republic of Indonesia. Thus, industrial relations are defined as the relationship between all parties with an interest in the process of producing goods or services in a company. The party with the most interest in the success of the company and in direct daily contact is the entrepreneur or the management with the workers/labourers.